Molière in Croatian Literary History and Literary Criticism (Molière u hrvatskoj kulturi, 2024)
The paper analyzes biographical, literary-historical, and literary-critical texts about Molière’s life and work published in the Croatian language in the period from the end of the 19th to the beginning of the 21st century. Their critical discourse is analyzed and the ways in which the mentioned author and his texts are presented and evaluated in them. The corpus of the analyzed texts comprises the texts by Alfred Orešković, Julije Adamović, Slavko Ježić, Ivo Hergešić, Helena Mandić Pachl, Nikola Batušić, and Višnja Machiedo. The aim of the paper is to describe Molière’s Croatian reception based on the analysis of the selected texts of literary history and literary criticism and to analyse the position of the French comediographer within Croatian literary history as well as cultural assumptions about him.